Qualitative Data Collection Methods - Tika Hestiarini Utami; Halimatus Sa’diyah; Faiqatul Munawwarah (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
This research aims to examine various methods that are often used in qualitative research. Qualitative data has the advantage of providing an in-depth understanding of the experiences, views and social context or individuals being studied. The method used in this research is library research where researchers obtain data from supporting literature and then analyze and describe it to make it easier to understand. The results of this research show that there are three qualitative data collection methods that are often used. The three methods are observation, interviews and documentation. Observation is used to observe existing phenomena and record the findings. Interviews are used to collect data by asking several questions to informants. And documentation is carried out to obtain data by utilizing written documents, archives, images, videos, and so on. These three collection methods have their respective advantages and disadvantages. It is hoped that this study can serve as a guide for researchers in choosing appropriate qualitative data collection methods to obtain a thorough and accurate understanding of the topic being researched.